Farmers' Response to the Use of Combine Harvester Machine on Rice Farming Business in Lojejer Village, Wuluhan Subdis-trict, Jember Regency - Famidayana, Lilis; Prayuginingsih, Henik; Aulia, Anisa Nurina (International Applied Science, 2024)
Rice is the most widely cultivated food crop commodity as the main food source in Indonesia. Efforts to increase rice production continue to be made to meet the food needs of the community in order to support food security. In line with the development of time, with the increasingly varied activities in the economy, agricultural technology is also growing. At this time the harvesting process which usually uses traditional rice harvesting tools is now switching to the use of modern combine harvester machines. This study aims to determine and analyse the response of farmers to the use of combine harvester and to determine the impact of the use of combine harvester on rice farming in Lojejer Village, Wuluhan District, Jember Regency. The study population was 120 farmers and became 32 samples using the slovin formula with a random sample method obtained from 16 farmers using combine harvester and 16 non-users of combine harvester. Data analysis method using likert scale method. The results showed that the response of farmers using combine harvester machines was in the criteria of high/responsive to very high/very responsive in terms of cost, yield optimisation, time efficiency, crop quality and job effectiveness.